Introduction: Moving to Nowhere Land? (Un)Certainties in transitions to work for the young generation - Christian Schröder (Social Work & Society, 2019)
Work has multiple important implications for individuals, social life and societies. "Work enables people to earn a livelihood and be economically secure. It is critical for equitable economic growth, poverty reduction and gender equality. It also allows people to fully participate in society while affording them a sense of dignity and worth." ('Human development report', 2015, p. 1) This special issue takes as it starting point the observation that there is an increase in transitions not only between workplaces but also between the status of being employed and being unemployed. The contributions in this special issue deal empirically with the questions of how increased demands on the successful management of transitions into work are negotiated discursively, how social work organisations deal with these issues, how the demands are experienced from the point of view of young people, and what chances they entail.